Factors Associated With Failure of Superior Pubic Ramus Screws. Issue 4 (April 2021) - Comadoll, Shea M.; Matuszewski, Paul E.; Liu, Boshen; Scott, Alesha; Cooper, Colin; Scott, Brandon; Wright, Raymond D.
Abstract : Objective: Examine factors associated with fixation failure in patients treated with superior intramedullary ramus screws. Design: Retrospective. Setting: Single, Level 1 trauma center. Patients: Unstable pelvic ring fractures amenable fixation that included superior intramedullary ramus screws. Intervention: Percutaneously inserted intramedullary superior ramus screw fixation of superior pubic ramus (SPR) fractures. Main Outcome Measurements: Loss of reduction (LOR) of the SPR fracture defined as >2 mm displacement on pelvic radiographs at any time point in follow-up. Results: Two hundred eighty-five fractures in 211 patients (age 44, 95% confidence interval 40.8%–46.4%, 59.3% women, 55.1% retrograde screws) were included in the analysis. 14 (4.9%) of fractures had LOR. Patients were significantly more likely to have LOR as age increased ( P = 0.01), body mass index (BMI) increased ( P = 0.01), and if they were women ( P < 0.01). There was a significantly decreased LOR ( P < 0.01) as fractures moved further from the pubis symphysis. Retrograde screws were significantly ( P < 0.01) more likely to have LOR. In SPR fractures treated with retrograde screws, failure was significantly associated with increasing BMI ( P = 0.02), the presence of an inferior ramus fracture ( P = 0.02), and trended toward significance with increasing age ( P = 0.06), and decreased distance from the symphysis ( P = 0.07). Conclusions: Superior ramus screws are associated with a low failure rate (4.9%), which is lower than previously reported. Retrograde screw insertion, distance from the symphysis, increasing age, increasing BMI, decreased distance from the symphysis, and ipsilateral inferior ramus fractures were predictors of failure. In these patients, alternative modalities should be considered, although low rates of failure can still be expected. Level of Evidence: Therapeutic Level IV. See Instructions for Authors for a complete description of levels of evidence. Abstract : Supplemental Digital Content is Available in the Text.